NFATc1 affects mouse splenic B cell function by controlling the calcineurin-NFAT signaling network - Bhattacharyya, Sankar; Deb, Jolly; Patra, Amiya K.; Duong Anh Thuy Pham; Chen, Wen; Vaeth, Martin; Berberich-Siebelt, Friederike; Klein-Hessling, Stefan; Lamperti, Edward D.; Reifenberg, Kurt; Jellusova, Julia; Schweizer, Astrid; et al. (Journal of Experimental Medicine, 2011)
By studying mice in which the Nfatc1 gene was inactivated in bone marrow, spleen, or germinal center B cells, we show that NFATc1 supports the proliferation and suppresses the activation-induced cell death of splenic B cells upon B cell receptor (BCR) stimulation. BCR triggering leads to expression of NFATc1/alpha A, a short isoform of NFATc1, in splenic B cells. NFATc1 ablation impaired Ig class switch to IgG3 induced by T cell-independent type II antigens, as well as IgG31(+) plasmablast formation. Mice bearing NFATc1(-/-) B cells harbor twofold more interleukin 10-producing B cells. NFATc1(-/-) B cells suppress the synthesis of interferon-gamma by T cells in vitro, and these mice exhibit a mild clinical course of experimental autoimmune encephalomyelitis. In large part, the defective functions of NFATc1(-/-) B cells are caused by decreased BCR-induced Ca2+ flux and calcineurin (Cn) activation. By affecting CD22, Rcan1, CnA, and NFATc1/alpha A expression, NFATc1 controls the Ca2+-dependent Cn-NFAT signaling network and, thereby, the fate of splenic B cells upon BCR stimulation.